Comparison of predicted and actual traffic data at pumas, UTHM by using UAV and SIDRA - Lim, Wei May; Abd Rahman, Raha; Hassan, Mohd Farid (Science and Engineering Research Support Society, 2020)
Urbanisation had causes congestion especially in urban area, traffic management and monitoring is important in easing the traffic impacts generated from rapid development together with land use planning to control development and redevelopment. Traffic impact assessment (TIA) provide the practitioner the framework for decision making but there is lacking of monitoring in the assessment after the development where congestion happens. Thus, this study proposed the use of unmanned aerial vehicle (UAV) and SIDRA intersection in data collection and analysis for traffic monitoring. The method of UAV video recording promotes accuracy and less complexity in traffic volume count. While, SIDRA intersection allows the analysis of level of service to determine the performance of the studied location. With this, the LOS of the intersection predicted for the year 2020 is compared with the actual traffic data taken. The Tjunction connecting minor road, J207 fronting PuMAS UTHM and the main road, FT005 was operating at LOS D in 2014 and in 2020 at LOS F during peak hours as predicted. Hence, sensor traffic signal is proposed to mitigate the congestion in the minor leg so that overall it will operate in LOS C.